The Pension Reform in Norway - a Useful Step, but More Funding Could be Beneficial - Gunnvald Grønvik (Norges Bank, 2006)
A reform of the fairly generous Norwegian public pension system was agreed upon by a broadly based coalition in the Norwegian Parliament in May 2005. The reform promises to reduce future costs and to improve labour incentives to work. The publicly provided pensions in Norway are of a PAYGO nature, with an exception for the supplementary pensions of the employees of the municipal sector. Norway is in an enviable economic situation. Even before the oil incomes started to accrue the financial position of the Norwegian public sector was good. Presently the oil-wealth is being converted to financial wealth on the public hands at a high pace. Current projections are that the fund accumulated from petroleum revenues shall exceed one year's gross domestic product in 2007. As en element of the pension reform this fund has been renamed to "The Government Pension Fund - Global". There also exists a "Government Pension Fund - Norway". These two funds are government property, and they have no specific task or obligation in providing the pensions. This paper outlines the main elements of the pension system in Norway and the reform, and illustrates a possible route for further reform. The extraordinary fiscal position of Norway can be used to create the initial fund in a (at least partially) funded pension system. Such a reform will reduce tax wedges and increase economic efficiency. Some implications for the Norwegian capital market and government budget are discussed.
hdl:11250/2508018
Keywords: 330